2016
DOI: 10.1016/j.jcta.2016.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Central limit theorems, Lee–Yang zeros, and graph-counting polynomials

Abstract: We consider the asymptotic normalcy of families of random variables X which count the number of occupied sites in some large set. We write Prob(X = m) = p m z m 0 /P (z 0 ), where P (z) is the generating function P (z) = N j=0 p j z j and z 0 > 0. We give sufficient criteria, involving the location of the zeros of P (z), for these families to satisfy a central limit theorem (CLT) and even a local CLT (LCLT); the theorems hold in the sense of estimates valid for large N (we assume that Var(X) is large when N is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 38 publications
2
32
0
Order By: Relevance
“…As a consequence, they gave a simple criterion for {X * n } to be asymptotically normal. Later, Lebowitz, Pittel, Ruelle and Speer (Henceforth LPRS) [20] studied a looser restriction on the roots that guarantees a central limit theorem for X n with large variance. They showed that if σ n n −1/3 → ∞, and none of the roots of {P n (z)} is contained in a neighbourhood of 1 ∈ C, then X n satisfies a central limit theorem.…”
Section: Resultsmentioning
confidence: 99%
“…As a consequence, they gave a simple criterion for {X * n } to be asymptotically normal. Later, Lebowitz, Pittel, Ruelle and Speer (Henceforth LPRS) [20] studied a looser restriction on the roots that guarantees a central limit theorem for X n with large variance. They showed that if σ n n −1/3 → ∞, and none of the roots of {P n (z)} is contained in a neighbourhood of 1 ∈ C, then X n satisfies a central limit theorem.…”
Section: Resultsmentioning
confidence: 99%
“…This condition is present in Lemma 6.4 from [LPRS16]. Already there, we do not know whether the condition is necessary.…”
Section: Resultsmentioning
confidence: 98%
“…From the definition of stability it may be shown that the generating polynomial for aX n + bY n has no zeros near 1 (this is Lemma 6.1 below). A result of [LPRS16] then implies a Gaussian approximation for aX n +bY n (Lemma 6.4 below). Tightness and continuity could be used to extend this to positive real (a, b), however the usual Cramér-Wold argument requires this for all real (a, b) regardless of sign.…”
Section: Resultsmentioning
confidence: 98%
“…As the 2 × 2 matrix integral operator J −1 A is not self adjoint, we have no immediate information as to the location of the zeros of the generating function. We note however that whenever the zeros of Ξ(z; J) come in complex conjugate paris whose real parts are non-positive, and σ J → ∞ then the process satisfies a CLT [23].…”
Section: Goe and Gsementioning
confidence: 91%